2016
DOI: 10.1186/s13041-016-0233-3
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing macrophage normal function in spinal cord injury with embryonic stem cell conditioned media

Abstract: BackgroundMacrophages play an important role in the inflammatory responses involved with spinal cord injury (SCI). We have previously demonstrated that infiltrated bone marrow-derived macrophages (BMDMs) engulf myelin debris, forming myelin-laden macrophages (mye-Mϕ). These mye-Mϕ promote disease progression through their pro-inflammatory phenotype, enhanced neurotoxicity, and impaired phagocytic capacity for apoptotic cells. We thus hypothesize that the excessive accumulation of mye-Mϕ is the root of secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…Nemeth et al observed that transplantation of human MSCs after SCI promoted functional recovery and modified the inflammatory environment by skewing macrophages into the anti-inflammatory M2 phenotype [ 47 , 48 ]. In addition, our previous data showed that ESC-conditioned media can effectively reduce lipid accumulation, promote an M2-like state and improve functional recovery after spinal cord injury [ 49 ]. In the present study, NSC transplantation improved functional recovery following SCI possibly due to the downregulation of M1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Nemeth et al observed that transplantation of human MSCs after SCI promoted functional recovery and modified the inflammatory environment by skewing macrophages into the anti-inflammatory M2 phenotype [ 47 , 48 ]. In addition, our previous data showed that ESC-conditioned media can effectively reduce lipid accumulation, promote an M2-like state and improve functional recovery after spinal cord injury [ 49 ]. In the present study, NSC transplantation improved functional recovery following SCI possibly due to the downregulation of M1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…109 Transplanted ESCs may form teratomas, which are constituted by cells from endodermal, mesodermal, and ectodermal lineages. [110][111][112] Recently, Guo et al 113 show that ESC-conditioned media can effectively reduce lipid accumulation, promote an M2-like state, and improve functional recovery after SCI. ESC-conditioned medium is sufficient to promote functional recovery in a murine model of SCI and avoids teratoma formation.…”
mentioning
confidence: 99%
“…Some studies considered the appropriate time for drug injection 8 hours after the spinal cord injury (16). Some experimental studies have not considered the use of high-dose MP for improvement of acute SCI (17,18). Our results revealed that the application of appropriate MP dose after SCI has positive effects on preventing infl ammation and cavity size in spinal cord.…”
Section: Discussionmentioning
confidence: 68%
“…Reverse transcription was carried out Step OnePlus™ Real-Time PCR System (Applied Biosystems, USA) with Syber Green PCR Master Mix (Applied Biosystems, USA) based on the company's guidelines under the following conditions: initial denaturation at 95˚C, denaturation at 95˚C for 30sec, annealing at 56˚C for 45sec, extension at 72˚C for 45sec and a fi nal polymerization at 72˚C for 10min.The primer sequences are brief in table 1. We applied the comparative a Ct method for gene target expression analysis (2ΔΔCt) (17). All samples normalized with GAPDH level, as the loading control (16).…”
Section: Qrt-pcrmentioning
confidence: 99%